2020
DOI: 10.1111/boc.201900093
|View full text |Cite
|
Sign up to set email alerts
|

Mechanobiology of antigen‐induced T cell arrest

Abstract: To mount an immune response, T cells must first find rare antigens present at the surface of antigen‐presenting cells (APCs). They achieve this by migrating rapidly through the crowded space of tissues and constantly sampling the surface of APCs. Upon antigen recognition, T cells decelerate and polarise towards the APC, ultimately forming a specialised interface known as the immunological synapse. These conjugates form as the result of the interaction between pairs of receptors/ligands that are under mechanica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 136 publications
0
5
0
Order By: Relevance
“…Each block contains a multi-head attention layer and a fully connected feedforward network, in which the multi-head attention mechanism is the core part of the overall framework, helping the model to grasp the information contained by the individual amino acids in the sequence and their relationships to each other. The attention score of a single head can be calculated using formula (1), where Q represents Query, K represents Key, V represents Value and dk represents the dimensionality of the Key. Attention(Q,K,V)=softmax(…”
Section: Overview Of Gratcrmentioning
confidence: 99%
See 1 more Smart Citation
“…Each block contains a multi-head attention layer and a fully connected feedforward network, in which the multi-head attention mechanism is the core part of the overall framework, helping the model to grasp the information contained by the individual amino acids in the sequence and their relationships to each other. The attention score of a single head can be calculated using formula (1), where Q represents Query, K represents Key, V represents Value and dk represents the dimensionality of the Key. Attention(Q,K,V)=softmax(…”
Section: Overview Of Gratcrmentioning
confidence: 99%
“…T cells, an integral part of the immune system, play a pivotal role in adaptive immunity by recognizing a diverse range of antigens [1,2]. This recognition is facilitated by the T cell receptor (TCR), a specialized cell surface protein crucial for antigen recognition and T cell activation [3].…”
Section: Introductionmentioning
confidence: 99%
“…A prerequisite to load distribution would be the physical coupling of the involved surface area. Along this line of reasoning, the biophysical parameters of membrane curvature and tension recently emerged as a possible mechanism influencing T-cell motility, protrusion, and immune synapse formation (reviewed in ( 126 )). The decisive physical parameter in this model is the modulation of membrane tension and tension decay at the triggering point, which could even be used to explain certain aspects of ligand discrimination ( 127 ) and synapse breaking ( 128 ).…”
Section: Mechanical Forces In T-cell Antigen Recognitionmentioning
confidence: 99%
“…Cell biological investigation of T cells derived from the immunodeficiency diseases has further led to insights into the roles of F-actin organizations at the immunological synapse. The results from these investigations have shown that polymerization of fresh filamentous actin (Factin) as well as F-actin remodeling assist various stages of synapse: in T cell migration, in formation of immunological synapse, in signaling at immunological synapse, as well as in regulating synapse duration (Chabaud et al, 2020;Colin-York et al, 2019a;Colin-York et al, 2019b;Comrie and Burkhardt, 2016;Kumari et al, 2013). At the immunological synapse, the spreading of T cell lamellae via cortical actin polymerization assists in increasing the surface contact area of a T cell with the antigen presenting cell (APC) to bolster antigen recognition.…”
Section: A U T H O R Accepted Manuscript Author Accepted Manuscriptmentioning
confidence: 99%